Knowledge, attitudes and practice of breast sonography among females at a rural health facility in Uganda - Aloysius Gonzaga Mubuuke (Inishmore Laser Scientific Publishing Ltd, 2019)
# Introduction Breast sonography has become an important evaluation tool in assessing breast masses and other suspicious breast changes. Despite its importance and popularity in many large hospitals, breast sonography remains under-utilized in many rural health facilities. # Objective The purpose of this study was to explore the knowledge, attitudes and practice of breast sonography amongst a group women in a rural health context. # Methods It was a cross-sectional study in which data from women was collected using interviewer-administered questionnaires. The qualitative component of the data was analysed using thematic analysis. For the quantitative component, SPSS was used for analysis. Association between socio-demographic characteristics and adequacy of knowledge, attitudes and practice of breast sonography were determined using both bivariate and logistic regression analysis. A Chi-square was used to test statistical significance. # Results Majority (95%) of the women in this study lacked knowledge of breast sonography, and generally all the women demonstrated a negative attitude towards breast sonography. Knowledge about breast sonography as well as recommendation by a health worker remained the only significant factors that seemed to influence the practice of seeking for breast sonography services. # Conclusions The women in this study demonstrated limited knowledge of breast sonography which perhaps contributed to the negative attitude and poor practice of seeking breast sonography services at the health facility.